2017
DOI: 10.1158/1541-7786.mcr-16-0432
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of PTK7 is Cytotoxic in Atypical Teratoid Rhabdoid Tumors

Abstract: Novel discoveries involving the evaluation of potential therapeutics are based on newly identified molecular targets for atypical teratoid rhabdoid tumors (ATRT), which are the most common form of infantile brain tumors. Central nervous system ATRTs are rare, aggressive, and fast growing tumors of the brain and spinal cord and carry a very poor prognosis. Currently, the standard of care for ATRT patients is based on surgical resection followed by systemic chemotherapy and radiation therapy, which result in sev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…Frizzled-7 (FZD7) is one of the receptors for Wnt signaling pathway 13 . It has been strongly confirmed that FZD7 is highly expressed in multiple cancers, including HCC 14 16 . And overexpressed FZD7 promotes the progression of cancers by inducing the activation of Wnt signaling pathway 13 , 17 .…”
Section: Introductionmentioning
confidence: 87%
“…Frizzled-7 (FZD7) is one of the receptors for Wnt signaling pathway 13 . It has been strongly confirmed that FZD7 is highly expressed in multiple cancers, including HCC 14 16 . And overexpressed FZD7 promotes the progression of cancers by inducing the activation of Wnt signaling pathway 13 , 17 .…”
Section: Introductionmentioning
confidence: 87%
“…The inhibition of PTK7 has been suggested as a novel therapeutic target for various cancers such as colorectal cancer and atypical teratoid rhabdoid tumors 31 , 32 , and some anticancer agents under development involve PTK7-targeted antibody-drug conjugates 33 or PTK7 aptamers 34 . However, caution should be used with this strategy when considering the evidence showing PTK7 can biphasically regulate tumorigenesis, as the inhibition of PTK7 activity or removal of PTK7-positive cells may induce tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of target proteins identified by analysis of the microarray data may be important targets for future therapies for medulloblastoma. As we have previously demonstrated, upregulation of PTK 7 may indicate that it is an important target for pediatric cancers [ 3 ]. LSD1, HDAC2, and HDAC3 are key targets for 4SC-202, and thus upregulation of these targets across the studied medulloblastomas makes 4SC-202 a more actionable therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few effectual treatments and surgery on children is not effective as the removal of the entire brain tumor is difficult. Recently, transcriptome profiling of malignancies of the central nervous system (CNS) have provided important insights into potential targets for therapies [ 2 , 3 , 4 ]. Here, we examine how transcriptome profiling of pediatric medulloblastomas reveals targets for potential therapies.…”
Section: Introductionmentioning
confidence: 99%